2017
DOI: 10.1037/per0000227
|View full text |Cite
|
Sign up to set email alerts
|

A quantitative and qualitative evaluation of trainee opinions of four methods of personality disorder diagnosis.

Abstract: Four methods of how to assess and diagnose personality disorders have received much attention within the literature: the Shedler-Westen Assessment Procedure (Shedler & Westen, 1998), the DSM-5 Section III Personality Disorders section (APA, 2011), the DSM-5 Section III trait model (APA, 2013), and the Psychodynamic Diagnostic Manual (PDM; PDM Task Force, 2006) descriptions of 15 personality disorders. Given that much of the debate has been driven by clinician concerns, it is important to consider clinical util… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
24
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 23 publications
(29 citation statements)
references
References 40 publications
5
24
0
Order By: Relevance
“…First, the respondents were requested to recall a familiar patient or client with whom they had worked with for at least 5 h and which they should keep in mind while completing the survey. Consistent with previous surveys on clinical utility, this 5‐h contact requirement was used in order to maximize the likelihood that respondents were sufficiently familiar with the patient to address diverse areas of personality functioning. To assist respondents in remembering their selected patient case, they were asked to provide an alias or nickname for the particular patient, which was used to prompt the respondent throughout the survey.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…First, the respondents were requested to recall a familiar patient or client with whom they had worked with for at least 5 h and which they should keep in mind while completing the survey. Consistent with previous surveys on clinical utility, this 5‐h contact requirement was used in order to maximize the likelihood that respondents were sufficiently familiar with the patient to address diverse areas of personality functioning. To assist respondents in remembering their selected patient case, they were asked to provide an alias or nickname for the particular patient, which was used to prompt the respondent throughout the survey.…”
Section: Methodsmentioning
confidence: 99%
“…Thus, the goal of the present study was to evaluate mental health professionals' perceived clinical utility of the ICD‐11 vs. ICD‐10 classification of PDs, when applied to one of their own patient cases. Consistent with the majority of the aforementioned studies, we investigated the perceived clinical utility in terms of (1) ease of use, (2) communication with other professionals, (3) communication with the patient, (4) describing all personality problems, (5) formulation of effective treatment and (6) describing the global personality …”
Section: Introductionmentioning
confidence: 99%
“…Studies actually indicate mixed findings about the support for dimensions over categories (Lowe & Widiger, 2009; Morey, Skodol, & Oldham, 2014 1 ; Rottman, Ahn, Sanislow, & Kim, 2009; Spitzer, First, Shedler, Westen, & Skodol, 2008). While a recent study (Nelson, Huprich, Shankar, Sohnleitner, & Paggeot, 2017) found that psychology graduate students and interns preferred the DSM-5 Section IIII trait ratings over categorical or prototype models, it also found that the Psychodynamic Diagnostic Manual (PDM) framework (PDM Task Force, 2006) was more appreciated for its comprehensiveness and that trainee age was positively correlated with favorable ratings of the PDM. These findings are consistent with a number of others that show that practicing clinicians with many years of experience find prototype models preferable to dimensional models.…”
Section: The Icd-11 Proposal: Limitations Of a Purely Dimensional Appmentioning
confidence: 99%
“…Contact information was obtained by examining lists of APA-accredited programs, and a request to forward the email to the students in their training program was sent. If the Director agreed, an email with a brief description of the purpose 1 While the trait method is a component of the Section III assessment methodology, we were interested in comparing a trait-only rating system with the specific Section III assessment methods [31] . and length of the survey was forwarded, and included a link to a Qualtrics survey.…”
Section: Methodsmentioning
confidence: 99%
“…First, we assessed only graduate students and intern trainees, and not experienced clinicians. It might be that increased clinical experience could influence trainees' orientation [31] . However, with a sample such as this, these findings report current trends in professional training and might be indicative of how the field is evolving with regard to personality disorder assessment.…”
Section: Limitations and Future Directionsmentioning
confidence: 99%